Hierarchical Porous Carbons Derived from Rice Husk for Supercapacitors with High Activity and High Capacitance Retention Capability. Issue 22 (9th August 2017) - Xiao, Yong; Zheng, Mingtao; Chen, Xun; Feng, Haobin; Dong, Hanwu; Hu, Hang; Liang, Yeru; Jiang, San Ping; Liu, Yingliang
Abstract: Hierarchical porous carbons (HPCs) were derived from rice husk biomass wastes via an effective HF treatment. HF treatment removes ash content and enhances the hierarchical porous structure of rice husk derived carbon with high electrochemical activity and high rate capacity for supercapacitors. The rice husk‐derived and HF treated HPCs exhibit a maximum capacitance of ca. 429 F g −1 at 0.5 A g −1 and excellent rate capability, reaching 240 F g −1 at an ultrahigh current density of 50 A g −1 . This is significantly better than 155 F g −1 at 50 A g −1 obtained on rice husk derived HPC but with no HF treatment. Moreover, the HF treated HPCs electrodes also exhibit good cycle stability over 95% capacitance retention after 20 000 cycles at a high charge current of 10 A g −1 . The increased rate of capacitance and rate capability of the HF treated HPCs based supercapacitors demonstrate that HF treatment is a simple and facile way to produce effective hierarchical structured carbons from natural biomass wastes with enhanced electrochemical performances for energy storage and conversion applications. Abstract : The rice husk‐derived and HF treated hierarchical porous carbons (HPCs) exhibit a maximum capacitance of ca. 429 F g −1 at 0.5 A g −1, excellent rate capability (240 F g −1 at even 50 A g −1 ), and good cycling life stability (5% loss after 20 000 cycles).